The Effect of Body Armor on Performance, Thermal Stress, and Exertion: A Crtical Review - Larsen, B.; Netto, Kevin; Aisbett, B. (Association of Military Surgeons of the U S, 2011)
Armed forces worldwide utilize some form of body armor as part of their personal protective system. This is particularly essential in recent times because of the increased sophistication of weapons employed during modern warfare and the advent of unconventional combat methods (such as the increased use of improvised explosive devices). There is some evidence to show, however, that the usage of military body armor impairs physical performance. This review of the literature will focus on the effect of body armor on the performance of, and physiological and subjective responses during, military-style physical tasks. Because of the paucity of research investigating body armor, this review will also draw upon more generalized personal protective clothing and equipment literature from a range of physically demanding occupations (i.e., firefighting and other emergency services). The review will conclude with suggested directions for future research in this area.